2012
DOI: 10.1159/000330035
|View full text |Cite
|
Sign up to set email alerts
|

Can a Brief Antepartum Preventive Group Intervention Help Reduce Postpartum Depressive Symptomatology?

Abstract: Background: Psychosocial and psychological interventions are generally effective in reducing depressive symptomatology in the postpartum period. Our aim was to evaluate the effectiveness of a brief preventive group intervention for postpartum depression (PPD) in a naturalistic setting, and study the effect of this on social and psychological risk factors. Methods: We conducted a randomized controlled trial (n = 1,719) in south-eastern Hungary in 62 antepartum centers. Pregnant women (n = 710) underwent a 4-ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 71 publications
(55 reference statements)
0
52
0
3
Order By: Relevance
“…l 37 trials reporting a universal preventive intervention 61,123,129,146,147,150,[153][154][155][156][157][180][181][182][183][184][185][186][187][197][198][199][200][207][208][209][210][211][212][217][218][219][220][225][226][227][228] l 20 trials reporting a selective preventive intervention 149,[158][159][160][161][162][163][188][189][190][191][192][201]…”
Section: Level Of Preventive Interventionmentioning
confidence: 99%
See 3 more Smart Citations
“…l 37 trials reporting a universal preventive intervention 61,123,129,146,147,150,[153][154][155][156][157][180][181][182][183][184][185][186][187][197][198][199][200][207][208][209][210][211][212][217][218][219][220][225][226][227][228] l 20 trials reporting a selective preventive intervention 149,[158][159][160][161][162][163][188][189][190][191][192][201]…”
Section: Level Of Preventive Interventionmentioning
confidence: 99%
“…[278][279][280]286 For ease of reference the universal preventive interventions have been given short-version descriptive labels ( Table 13). 155 Three studies provided the intervention using a group format, [154][155][156] whereas two involved individual sessions 61,153 and one combined both group and individual sessions. 157 Two trials provided interventions in the home setting, 61,153 whereas in the other four trials the intervention was provided in the antenatal setting.…”
Section: Description Of Qualitative Studies Of Universal Preventive Imentioning
confidence: 99%
See 2 more Smart Citations
“…To date, research has concluded that compared to White mothers and mothers from privileged backgrounds, mothers of color have lower incomes (Dagher, McGovern, Dowd, & Gjerdingen, 2012;Feder et al, 2009;Kozinsky et al, 2012;Lara et al, 2015), lower levels of education (Dagher et al, 2012;Lanes, Kuk, & Tamim, 2011), higher rates of unemployment (Boyce & Hickey, 2005;Dagher et al, 2012;Janssen, Heaman, Urquia, O'Campo, & Thiessen, 2012), greater likelihood of single parenting (Boyce & Hickey, 2005;Lewin, Mitchell, & Ronzio, 2013), and worse housing conditions (Cutrona et al, 2005;Jacobs, 2011;Redshaw & Henderson, 2013). Moreover, mothers of color generally have higher rates of chronic diseases such as diabetes mellitus and hypertension (Kim et al, 2014), are more likely to have inadequate health insurance (Blumenthal & Collins, 2014), and have poorer access to adequate healthcare (Orr, Reiter, James, & Orr, 2012) than other mothers.…”
Section: The Varying Rates Of Postpartum Depressionmentioning
confidence: 99%